Trends and Patterns in Mandible Bone Cancer Research: An Updated Comprehensive Bibliometric Review - Arabion, Hamidreza; Khosronejad , Arya; Afshar , Alireza; Iraji, Aida; Mokhtarzadegan, Mohamad; Aliabadi , Ehsan; Ebrahimi , Reyhaneh; Mussin, Nadiar M.; Kurmanalina, Madina A.; Tanideh , Nader; Tamaddon, Amin (Galen Medical Journal, 2024)
Background: Mandible bone cancer, while relatively rare, poses significant challenges due to its aggressive nature and the complex treatment required. This bibliometric review aims to analyze the trends and patterns in mandible bone cancer research from 1933 to 2024, providing insights into the evolution of scholarly contributions and the impact of various studies in this field. Materials and Methods: Data were collected from the Web of Science Core Collection and Scopus databases, focusing on articles published between 1933 and 2024. A total of 8,093 articles were analyzed, with performance metrics evaluated using RStudio and the bibliometrix R-package. Key metrics included publication growth, citation analysis, and keyword frequency assessment. Results: The analysis revealed a steady annual growth rate of 6.05% in publications, with significant contributions from institutions such as the University of California and Tokyo Medical and Dental University. The average citation per manuscript was 18.41, indicating robust engagement with the literature. Key themes identified included mandible, mandibular reconstruction, and osteoradionecrosis, reflecting ongoing research interests and collaborative networks among authors. Conclusion: This review highlights the increasing scholarly attention on mandible bone cancer, emphasizing the need for continued research to address existing gaps in diagnosis and treatment. Collaborative efforts among institutions and researchers will be crucial in advancing the understanding and management of this complex disease, ultimately improving patient outcomes.